BEYOND BINARY: A GENDER AND LINGUISTIC ANALYSIS OF THE RECONSTRUCTION OF PRONOUN 'THEY' - Noviana, Ananda Putri; Indah, Rohmani Nur (Annual International Conferences on Language, Literature, and Media, 2023)
Gender discrimination occurs when individuals are consistently referred to using gender-specific pronouns, such as 'he' or 'she,’ irrespective of their expressed gender identity or preference. This study examines the correlation between gender and sociolinguistic theory in constructing the pronoun 'non-binary singular they' in English. Additionally, it analyzed the factors that impact individuals' responses to its usage to propose a more appropriate approach to addressing and using ‘non-binary singular they’ to mitigate discrimination. This study employed a qualitative descriptive approach and utilized gender equity and sociolinguistic theories for the analysis. This study conducted comprehensive library research with a conceptual framework of a literature review using secondary data. The study results showed that the concept of gender and sociocultural factors play a central role in the reconstruction of the use of the pronoun 'non-binary singular they.’ In addition, understanding the English language and social attitudes towards non-binary individuals can influence their level of acceptance of the use of the pronoun 'non-binary singular they.' This finding also indicates that the higher the level of understanding of the English language and the concept of gender, and the more frequently involved with non-binary individuals, the higher the support for the use of 'non-binary singular they.’ Therefore, efforts to increase an in-depth understanding of English and the concept of gender are essential to realizing gender equality through gender-inclusive pronouns: ‘they.’